A systematic review of physical activity: benefits and needs for maintenance of quality of life among adults with intellectual disability - Jacob, Udeme Samuel; Pillay, Jace; Johnson, Ensa; Omoya, Oluwatomilayo (Tomi); Adedokun, Adewale Philip (Frontiers in Sports and Active Living, 2023)
The inactivity of people with intellectual disabilities (PwID) is a major contributor to ill health. Probably because people with intellectual disabilities are not adequately informed about physical activity and intervention programs required to enhance their fitness. This study critically reviewed physical activity: benefits and needs for maintenance of quality of life among adults with intellectual disability. An extensive search of bibliographic databases such as PubMed, PsycINFO, BioMed Central and Medline identified 735 academic papers. The research rigour was evaluated, and the validity of the findings was established. Based on the inclusion criteria, 15 studies were included in the review. Various forms of physical activity were studied as interventions. The results of a critical review indicate that physical activity has a moderate to strong positive impact on weight loss, sedentary behaviour, and disability-related quality of life. Adults with ID may benefit from physical activity as a non-pharmaceutical method of improving their health needs. However, this study's results may only apply to some adults with intellectual disabilities. The sample size needs to be increased in future studies in order to draw generalizable conclusions.